Evaluation of team communication in an interprofessional inpatient transition of care simulation - Michelle L. Blakely; Lauren Biehle (Elsevier, 2021)
Background: Interprofessional education (IPE) provides unique opportunities for students to better understand their roles, roles of other healthcare professionals, and prepare for teamwork for patient benefit. Interprofessional team education is recognized as a key element in the 2016 ACPE standards. Objective: Assess student self-perceived competence in four IPEC domains after an inpatient simulation activity. Methods: Pre/post-test design used the Interprofessional Education Collaborative Competency Survey. The activity included medical, nursing, social work, and pharmacy students working in healthcare teams to develop collaborative treatment plans for simulated patients with altered mental status. Results: Ninety-seven health profession students completed the activity, while 49 second-year (P2) student pharmacists participated in the study. All completed a pre-test and 47/49 (96%) completed a post-test. At pre-test, students ranked themselves highest in abilities to respect patient privacy (100% strongly agree) and acting with honesty and integrity in relationships (100% strongly agree). They reported lower ability in describing team development process. At post-test, significant increases were seen in managing ethical dilemmas (p < .002) and respect (p = .49), though decreases were seen in using appropriate or respectful language (p < .02). Conclusion: Significant differences in student perceptions of ethics and communication were observed after participation in a transition of care inpatient IPE simulation.